2014
DOI: 10.1016/j.alcohol.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of one- and three-day binge alcohol exposure in neonatal C57BL/6 mice on spatial learning and memory in adolescence and adulthood

Abstract: Binge-like alcohol exposure during the early postnatal period in rats and mice causes deficits in spatial learning and memory that persist into adulthood. Wozniak et al. (2004) reported that heavy binge alcohol exposure on postnatal day 7 (PD 7) in C57BL/6 (B6) mice produced profound spatial learning deficits in the Morris water maze when tested in adolescence (P30–39); when tested in adulthood, however, the deficits were greatly attenuated. Using a similar PD 7 binge alcohol exposure paradigm in B6 mice, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…Studies have reported either less retention (An & Zhang, 2013; Gianoulakis, 1990; Wagner et al, 2014; Wozniak et al, 2004) or no change compared to controls (Dursun et al, 2006; Goodlett & Johnson, 1997; Wagner et al, 2014; Wozniak et al, 2004). Only one study reports decreases in probe task memory without accompanying altered learning (Zink et al, 2011).…”
Section: Learning Memory and Executive Control (Cognitive)mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported either less retention (An & Zhang, 2013; Gianoulakis, 1990; Wagner et al, 2014; Wozniak et al, 2004) or no change compared to controls (Dursun et al, 2006; Goodlett & Johnson, 1997; Wagner et al, 2014; Wozniak et al, 2004). Only one study reports decreases in probe task memory without accompanying altered learning (Zink et al, 2011).…”
Section: Learning Memory and Executive Control (Cognitive)mentioning
confidence: 99%
“…The majority of the studies reviewed here were completed using the Morris water maze (MWM) task and measured both acquisition of a spatial memory and retention of the spatial memory during probe trials. There is a clear detrimental effect of PAE across a variety of doses, exposure times, and testing ages on acquisition during the MWM (An & Zhang, 2013; Dursun, Jakubowska-Doğru, & Uzbay, 2006; Gianoulakis, 1990; Girard, Xing, Ward, & Wainwright, 2000; Goodlett & Johnson, 1997; Means, Russ, Medlin, & Gray, 1986; Wagner, Zhou, & Goodlett, 2014; Wozniak et al, 2004). However, moderate doses, particularly during gestation, do not reliably impact learning and memory in either the MWM or Y-maze task (Cullen, Burne, Lavidis, & Moritz, 2014; Hamilton et al, 2014; Sanchez Vega, Chong, & Burne, 2013).…”
Section: Learning Memory and Executive Control (Cognitive)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Morris water maze (MWM) task was conducted following a previously published protocol (Wagner, Zhou, & Goodlett, 2014). The mice began training in the water maze at ~60 days of age, by an experimenter blind to treatment and genotype.…”
Section: Morris Water Maze Place Learning Task (Mwm)mentioning
confidence: 99%
“…Litters had 2–4 males, hence there were 1 or 2 males from the same litter per treatment combination. Dose was chosen based on the literature (Ieraci and Herrera, 2007; Ikonomidou et al, 2000; Lantz et al, 2012; Wagner et al, 2014; Wozniak et al, 2004). On PD21, all mice were weaned into groups of four by sex (Fig.…”
Section: Methodsmentioning
confidence: 99%